O rodzajach przerzutni - Wyderka, Bogusław (Stylistyka, 1998)
The problems discussed in the article concern the typology of enjambement in Polish syllabic verse. According to the suggestion offered , enjambement appears due to the coincidence ofseveral phenomena which differ as to their status in the system oflanguage. These are: suspension ofthe sentence intonation pattern, prosodic character ofthe segmented phrase, connotational signal sent by the element left in the enjambement line and the pauses signalling syntactic borders. A bundle of coinciding factors which form a changing hierarchy determines the differences between constructional variants of the figure. Over a dozen types of enjambement has been distinguished. The method of analysis together with a quantitative description makes it possible to characterise precisely the investigated material. The results obtained using the proposed tools make it possible both to describe the general tendencies in the development of enjambement as a poetic style phenomenon and to determine individual preferences ofthe artists. The sam[1]ple analysis deals with the rich material of Polish Renaissance poetry.